A perspective on erythropoietin as a potential adjuvant therapy for acute lung injury/acute respiratory distress syndrome in patients with covid-19 (2020)
The novel coronavirus 2019-nCoV (SARS-CoV-2) infection that emerged in China in December 2019 has rapidly spread to become a global pandemic. This article summarizes the potential benefits of erythropoietin (EPO) in alleviating SARS-CoV-2 pathogenesis which is now called COVID-19. As with other coronavirus infection, the lethality of COVID-19 is associated with respiratory dysfunction due to overexpression of proinflammatory cytokines induced by the host immune responses. The resulting cytokine storm leads to the development of acute lung injury/acute respiratory distress syndrome (ALI/ARDS). Erythropoietin, well known for its role in the regulation of erythropoiesis, may have protective effects against ALI/ARDS induced by viral and other pathogens. EPO exerts antiapoptotic and cytoprotective properties under various pathological conditions. With a high safety profile, EPO promotes the production of endothelial progenitor cells and reduce inflammatory processes through inhibition of the nuclear factor-kB (NFkB) and JAK-STAT3 signaling pathways. Thus, it may be considered as a safe drug candidate for COVID-19 patients if given at the early stage of the disease. The potential effects of erythropoietin on different aspects of ALI/ARDS associated with SARS-CoV-2 infection are reviewed.